Contrasting Levels of Molecular Evolution on the Mouse X Chromosome. Issue 4 (1st August 2016) - Larson, Erica L; Vanderpool, Dan; Keeble, Sara; Zhou, Meng; Sarver, Brice A J; Smith, Andrew D; Dean, Matthew D; Good, Jeffrey M
Abstract: The mammalian X chromosome has unusual evolutionary dynamics compared to autosomes. Faster-X evolution of spermatogenic protein-coding genes is known to be most pronounced for genes expressed late in spermatogenesis, but it is unclear if these patterns extend to other forms of molecular divergence. We tested for faster-X evolution in mice spanning three different forms of molecular evolution—divergence in protein sequence, gene expression, and DNA methylation—across different developmental stages of spermatogenesis. We used FACS to isolate individual cell populations and then generated cell-specific transcriptome profiles across different stages of spermatogenesis in two subspecies of house mice ( Mus musculus ), thereby overcoming a fundamental limitation of previous studies on whole tissues. We found faster-X protein evolution at all stages of spermatogenesis and faster-late protein evolution for both X-linked and autosomal genes. In contrast, there was less expression divergence late in spermatogenesis (slower late) on the X chromosome and for autosomal genes expressed primarily in testis (testis-biased). We argue that slower-late expression divergence reflects strong regulatory constraints imposed during this critical stage of sperm development and that these constraints are particularly acute on the tightly regulated sex chromosomes. We also found slower-X DNA methylation divergence based on genome-wide bisulfite sequencing of sperm from two species of mice ( M. musculus and M. spretus ), although it is unclear whether slower-X DNA methylation reflects development constraints in sperm or other X-linked phenomena. Our study clarifies key differences in patterns of regulatory and protein evolution across spermatogenesis that are likely to have important consequences for mammalian sex chromosome evolution, male fertility, and speciation.